Cognitive Multi-agent Systems Structures, Strategies and Applications to Mobile Robotics and Robosoccer - Hajduk, Mikuláš; Sukop, Marek; Haun, Matthias; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The book describes an approach to the multi-agent systems (MAS) design for applications of robotic soccer in the MiroSot category. The described MAS is designed for dynamic, quickly changing environments, in which not only the actions of our MAS are observed, but also those of the opposing MAS. It actively tries to affect the environment to score goals faster than the opposing MAS. Multi-agent systems (MAS) are mostly applied in the environments in which they exist and act without an opposing system. The book also describes strategies based on a supervisor that makes decisions depending on behavior prediction of the opposing MAS and the ball movement in the working place. A sophisticated distribution of tasks was designed for each agent to cooperate in order score goals as fast as possible. Simultaneously, these agents try, by permitted means, to prevent the enemy agents from scoring goals. The approach described is an excellent guide to the constantly evolving abilities of mobile robotics, both for real-world applications, such as cooperation of multiple robots in life-saving activities, and for the steadily developing applications of mobile robots in various robotic competitions (e.g. Robocup, etc.). The book provides readers with high-level knowledge on how to design strategies and how to implement such systems, and the ideas presented enable them to further refine the approach utilizing the latest hardware and use it in new systems implementations of sophisticated intelligent engineering.
Introduction -- MAS properties and classification -- Agent approach to multi-agent systems -- Multi-agent system application in robosoccer -- Hierarchical arrangement of the agents in developed MAS and its strategic concept -- Elementary agents players and their assignment to robots.
Keywords: Computational intelligence; Artificial intelligence; Control engineering; Robotics; Automation; Automotive engineering; Computational Intelligence; Artificial Intelligence; Control, Robotics, Automation; Automotive Engineering